2021
DOI: 10.3390/healthcare9010076
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Attitude, Barriers/Facilitators, and Visual Differentiation on Oral Mucosa Pressure Ulcer Prevention Performance Intention

Abstract: Oral mucosa pressure ulcers (PUs) can result in frequent pain and discomfort, and have negative effects on quality of life. We aimed to examine attitude, barriers/facilitators of oral mucosa PU prevention, the ability to differentiate oral mucosa PU, and to identify factors influencing PU prevention performance intention. This was a cross-sectional descriptive study of 112 nurses in seven tertiary hospitals and three secondary hospitals. The data collection period was from August to December 2018. For data ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…PI nursing knowledge is positively correlated with PI nursing attitudes, and PI nursing attitudes are positively correlated with PI nursing performance [25,35], while other studies have shown no correlation between PI nursing performance and PI nursing knowledge [36]. The results of these studies suggest many complex factors regarding the relationship between PI nursing knowledge and PI nursing practice.…”
Section: Discussionmentioning
confidence: 93%
“…PI nursing knowledge is positively correlated with PI nursing attitudes, and PI nursing attitudes are positively correlated with PI nursing performance [25,35], while other studies have shown no correlation between PI nursing performance and PI nursing knowledge [36]. The results of these studies suggest many complex factors regarding the relationship between PI nursing knowledge and PI nursing practice.…”
Section: Discussionmentioning
confidence: 93%